Five-Year Follow-up of Nonfibrotic Scars in the Comparison of Age-Related Macular Degeneration Treatments Trials - Daniel, Ebenezer; Ying, Gui-Shuang; Kim, Benjamin J; Toth, Cynthia A; Ferris, 3rd, Frederick; Martin, Daniel F; Grunwald, Juan E; Jaffe, Glenn J; Dunaief, Joshua L; Pan, Wei; Maguire, Maureen G (Ophthalmology (Rochester, Minn.), 2019)
To describe changes in visual acuity (VA) and macular morphologic features at 5 years in eyes with nonfibrotic scar (NFS) identified at 1 year in the Comparison of Age-Related Macular Degeneration Treatments Trials (CATT). Prospective cohort study within a randomized clinical trial. Participants in CATT. Participants assigned to ranibizumab or bevacizumab and to 1 of 3 dosing regimens were released from the clinical trial protocol after 2 years and recalled at 5 years. Nonfibrotic scar was identified on color images at year 1 as flat, small, well-circumscribed areas of pigmentation with varying degrees of central hypopigmentation without exposure of underlying choroidal vessels at the site of baseline choroidal neovascularization. Follow-up images were assessed for changes in and around NFS. Pigmentation changes, VA, development of fibrotic scar (FS), nongeographic atrophy (NGA), geographic atrophy (GA), retinal fluid on OCT, and fluorescein leakage. Among 474 eyes with images obtained at 1, 2, and 5 years, 39 (8.2%) showed NFS at 1 year with a mean VA of 80 letters (Snellen equivalent, 20/25). Among these eyes, FS developed in 5% at 2 years and 28% at 5 years. Nongeographic atrophy was observed in 34%, 47%, and 65% of eyes at 1, 2, and 5 years, respectively. Geographic atrophy developed in 5% of eyes at 2 years and 21% at 5 years. Among eyes with NFS, FS, or no scar at 1 year, mean VA at 5 years was 73 letters (20/32), 48 letters (20/100), and 62 letters (20/63), respectively. At 5 years, NFS eyes demonstrated less GA, less intraretinal fluid, more subretinal fluid, and less subretinal pigment epithelium fluid (all P < 0.01). Among NFS eyes, mean thickness of the retina, subretinal tissue complex, and total retina did not change across years 1 to 5 (P > 0.50). The proportion of eyes with fluid on OCT also did not change (P = 0.36). Subretinal hyperreflective material disappeared by 5 years in 40% of eyes with NFS. These results indicate that, on average, eyes with NFS after anti-VEGF treatment have good VA not only at 1 and 2 years, but also through 5 years.